THE RESPONSIVENESS OF SEXUAL OFFENDERS TO A THERAPEUTIC GROUP WORK PROGRAMME AT WESTVILLE MEDIUM B PRISON - Mathe, Sibonsile (Social Work/Maatskaplike Werk, 2007)
The scientific study of crime, has engaged the interest of many disciplines, just as professional work with offenders has drawn on the contributions of various professions, including social work. Sexual offences are among the crimes that invoke the most fear and concern. In addition to the human costs in terms of emotional and physical anguish and suffering, staggering financial costs are incurred as a result of child welfare and juvenile and criminal justice system involvement, therapeutic intervention and preventive efforts (Prentky & Burgess, 1990).